Rhizobium inocula effect in common bean (Phaseolus vulgaris L.). - Hernández, Germán; Sánchez, Mercedes; Toscano, Vidalina; Méndez, Nancy; Mullings, Miguel (Agronomía Mesoamericana, 2015)
Strains of Rhizobium CR 113; CR 477; CF-1 (equal to CIAT 151); 6bIII; 2bIII and HbI, along with noninoculated and non-nitrogenated treatments – 30 kg/ha N without inoculation and high N, 150 kg/ha N – in three environments in the Pinar del Rio, Matanzas and Holguin provinces were validated in three types of soil: ferrous quartzitic, ferrous red, and non- carbonated brown with a low total nitrogen content (less than 65kg/ha N). The BAT 58 bean variety was used. Production of aerial and nodular dry matter during the development phase (R6), production of aerial dry matter and total nitrogen consumption in the (R8) phase, and bean production in the (R9) phase, were quantified. Results showed a lower significant difference in the treatments without inoculation, as compared to the treatments with high nitrogen content and 30kg/ha N plus seed inoculation. No difference was found between the treatment with high N applications, and the ones inoculated with Rhizobium strains plus 30 kg/ha.